Lexicon of Medicinal Plant in Gayo Ethnic - Fathul Jannah Harahap; Namira Az-Zahra; Tasnim Lubis (Tradition and Modernity of Humanity, 2025)
The purpose of this study is to identify and describe the ethnobotanical lexicon of traditional medicine of the Gayo community and to understand its lexical meaning based on the ecological and cultural experiences inherent in the speech of the community. This study uses a qualitative approach to explore and understand the meaning of individuals or groups derived from social problems, with a focus on the natural context and descriptive data such as words or pictures. Based on the results of the research that has been conducted, it can be concluded that the Gayo community in Blangkejeren has a wealth of lexicon in local languages ​​that are closely related to traditional medicine practices. These lexicons reflect not only linguistic knowledge, but also local knowledge that is passed down from generation to generation.